Does exposure to university researchers improve undergraduate perceptions of research?: A quasi cluster-randomized controlled trial. Issue 6 (1st November 2020) - Gennis, Hannah; DiLorenzo, Miranda; Pillai Riddell, Rebecca; Spiegel, Rebecca; Connolly, Jennifer; Martin, Jodi
ABSTRACT: This study explores the impact of talks by university researchers in different formats on students' perceptions of research. Undergraduate students ( N = 222) were randomly assigned to watch research talks via video recording ( n = 78), research talks presented live ( n = 67), or a control group ( n = 77). Students completed pre-intervention (Time 1) and post-intervention (Time 2) questionnaires on their perceptions of 1) university-specific research, 2) psychology-specific research, and 3) general research. Analysis of Variance (ANOVA) testing revealed that at Time 2, the video intervention group had significantly more positive perceptions about research compared to the control group. Several barriers to research involvement were noted, including competitiveness, lack of interest, lack of knowledge, and time constraints. Enhancing the undergraduate curriculum by integrating university researchers into the classroom is a potentially innovative way to introduce and promote research interests in students.